Development of Interactive Multimedia Based on Appy Pie to Improve Learning Outcomes of Elementary School Students - Zikri Wildan Setiadi; Aldina Eka Andriani (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop, test the feasibility and effectiveness of interactive multimedia based on Appy Pie to improve the cognitive learning outcomes of students in grade V of SD Negeri Kemijen 02, Semarang City. This type of research is development research (R&D) using the ADDIE model. The subjects of the study were 27 students in grade V of SD Negeri Kemijen 02. Data collection techniques include non-test and test. The data analysis technique uses normality test, homogeneity test, t-test, and N-Gain test. The results showed that the Appy Pie-based interactive multimedia development included covers, instructions for use, concept maps, learning competencies, materials, videos, discussion pages, AI chatbots, and evaluations. The feasibility results of media experts are 97.91% "very feasible", material experts are 89.28% "very feasible". The effectiveness of multimedia is proven through the t-test which shows a significance value of 0.000 (<0.05) with an N-gain value of 0.68 in the medium category. This study concludes that Appy pie-based interactive multimedia has been successfully developed with a very feasible and effective category to improve the learning outcomes of IPAS for grade V students of SD Negeri Kemijen 02 Semarang City.